DISFONIA PADA PASIEN DENGAN PARESIS UNILATERAL PLIKA VOKALIS : LAPORAN KASUS - Munasiah, Melia; Novtarina, Rizki; Fedriani, Fivien (Medula, 2024)
Hoarse voice (dysphonia) is one of the reasons for consultation (1%) in all primary health services. Vocal cord paralysis is reduced movement or paralysis of the vocal cords. This situation is a manifestation of disease that occurs in the cranial cavity, larynx, thorax and mediastinum which causes paralysis of the vagus nerve and recurrent laryngeal nerve. Mr. I, a 56 year old male, came with complaints of sudden loss of voice. Complaints appeared 11 days before admission to the hospital (SMRS). Another complaint that is felt is that patients choke more easily when drinking. Complaints are felt to be getting worse day by day. The patient had previously been given antibiotics and anti-inflammatory drugs given at the puskesmas but there was no improvement either. The patient was previously hospitalized due to complaints of excessive vomiting. The patient's general status is within normal limits. LFO results showed adductor type unilateral paramedian vocal fold paralysis in the dextra paramedian position. The patient was given a physiotherapy plan and given steroids and vitamin B12. Voice therapy can be an effective treatment option in patients with unilateral paresis of the vocal folds and should be considered individualized according to the patient's age.